2020
DOI: 10.1089/ast.2019.2025
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Preservation of Microbial Palisade Fabric in Silica Deposits from El Tatio, Chile

Abstract: Palisade fabric is a ubiquitous texture of silica sinter found in low temperature (<40°C) regimes of hot spring environments, and it is formed when populations of filamentous microorganisms act as templates for silica polymerization. Although it is known that postdepositional processes such as biological degradation and dewatering can strongly affect preservation of these fabrics, the impact of extreme aridity has so far not been studied in detail. Here, we report a detailed analysis of recently silicified pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 77 publications
0
41
0
Order By: Relevance
“…Those organisms coexist with cyanobacteria at temperatures from 60°C to 65°C in Yellowstone, USA, and Iceland (e.g., Steinke et al, 2020; Van Der Meer et al, 2007). In El Tatio, these bacteria were found in lower temperature (~40°C) bacterial mats, with δ 13 C between −13‰ and −16‰ (Gong et al, 2020). Incorporation of inorganic carbon would yield old apparent 14 C ages as in magmatic environments with high CO 2 emissions (Evans et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Those organisms coexist with cyanobacteria at temperatures from 60°C to 65°C in Yellowstone, USA, and Iceland (e.g., Steinke et al, 2020; Van Der Meer et al, 2007). In El Tatio, these bacteria were found in lower temperature (~40°C) bacterial mats, with δ 13 C between −13‰ and −16‰ (Gong et al, 2020). Incorporation of inorganic carbon would yield old apparent 14 C ages as in magmatic environments with high CO 2 emissions (Evans et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Di Benedetto et al, 2011) or to Leptolyngbya (cf. Valeriani et al, 2018; Gong et al, 2020) and to Synechococcus (Pentecost, 2003), respectively. Pentecost and Coletta (2007) identified Spirulina labyrinthiformis as the most abundant cyanobacteria from temperatures < 54°C, associated with Fischerella laminosus , Oscillatoria cf.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Nevertheless, the three sites show that there is a temperature control on the composition of the microbial mats and within the same system from proximal to distal cooled-down settings (Figure 12). Various studies have suggested a temperature control on the composition of microbial communities in hydrothermal terrestrial settings (Cady and Farmer, 1996; Farmer, 2000; Dunckel et al, 2009; Di Benedetto et al, 2011; Djokic et al, 2017; Des Marais and Walter, 2019; Sanchez-Garcia et al, 2019; Gong et al, 2020).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen microfossils from the Wobegong North sinters, located within the Conway Hydrothermal System in Drummond Basin, displaying thin-bedded palisade fabrics (a common texture of silica sinter formed by populations of filamentous microorganisms [ 26 ]), were chosen for analyses [ 24 ]. Microfossils were located and imaged via transmitted light microscopy ( Supplementary Materials ) and were analyzed via confocal laser scanning microscopy to confirm features commonly associated with microbial remains (e.g., fluorescent cell walls, hollow structure—see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%